Waste Management System from The Remaining Machining Production at PT Astra Honda Motor Plant 1 Sunter North Jakarta - Arham Iqbal Fatama; Indah Wahyu Utami; Arry Hutomo; Maaz Ud Din; Tri Wisudawati (LPPM Universitas Duta Bangsa Surakarta, 2021)
Currently, the industry is growing rapidly both in variety and quantity in Indonesia. Each industry has the potential to produce waste resulting from its production process. All parts of the production process produce waste, both recyclable and non-berguna.PT waste. Astra Honda Motor Indonesia produces hazardous and toxic waste from production process activities and can potentially become a pollutant for the environment if not managed properly. Raw materials used in PT. AHM Plant 1 to produce motorcycles is Aluminum Ingot and Plastic Ore so that waste is produced by the rest of the production from PT. Astra Honda Motor Indonesia itself in the form of ash, coolant, scrap aluminum, paint crust, die lube, gases. Pt. Astra Honda Motor Indonesia manages waste management well so that it does not pollute the environment.